Answer: -22
==========================================================
Step-by-step explanation:
You could use synthetic division or polynomial long division to find the answer, but a much quicker way is to apply the remainder theorem.
That theorem says that if we divide p(x) over (x-k), then the remainder is p(k).
We're dividing over x+3, or x-(-3), so we can see that k = -3 in this case.
Plug this into the function
f(x) = x^3+5
f(-3) = (-3)^3 + 5
f(-3) = -27 + 5
f(-3) = -22 is the remainder
------------
If you want to use polynomial long division or synthetic division, then check out the diagram below.